From experience to engagement: a mixed methods exploration of learning environments using artificial intelligence and extended reality - Hmoud, Mohammad; Daher, Wajeeh; Ayyoub, Abedalkarim (Frontiers in Education, 2025)
Student engagement significantly influences academic success, motivating educators to explore innovative technologies to enhance learning environments. This mixed-methods study systematically investigates the impact of Artificial Intelligence, Extended Reality, and their combined usage, compared with traditional learning environments, on high school students' cognitive, emotional, behavioral, and social engagement. Utilizing Kolb's Experiential Learning Theory, this research used a convergent parallel design, combining quantitative data from 888 students who took part in rigorous non-parametric analyses and semi-structured interviews with 40 students sampled for qualitative descriptive thematic analysis. Results indicated that the AI-XR environment outperformed all other environments across all four engagement categories. Findings reinforce the synergistic opportunities for learning with AI and XR when applied in educational environments. The XR environment conceptually yielded higher levels of emotional and cognitive engagement through the immersive visualization, while the AI-environment yielded high levels of personalized adaptive learning pathways for students. Meanwhile, traditional learning environments led to the lowest engagement levels, due to their passive and non-interactive teaching nature. These findings reveal the transformative power of combining AI and XR technologies, offering essential implications for teachers, policymakers, and instructional designers committed to fostering deeper and broader student engagement in the context of digitally enriched educational systems.